TEACHER STRATEGIES IN SHAPING THE DISCIPLINARY CHARACTER OF GRADE V STUDENTS AT MIS BINA DHARMA PARIT WEDNESDAY, TELUK KERAMAT DISTRICT - Maulida, Maulida; Ridwan, Yayan; Saripah, Saripah (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This thesis discusses Teacher Strategies in Shaping the Disciplinary Character of Class V Students at MIS Bina Dharma Parit Rabu. This research has three research objectives including the following: First, to find out how the teacher's strategy in shaping the disciplinary character of grade V students at MIS Bina Dharma Parit Rabu Teluk Keramat District. Second, to find out how the disciplinary character of grade V students at MIS Bina Dharma Parit Rabu Teluk Keramat District. Third, to find out what are the supporting and inhibiting factors in shaping the disciplinary character of grade V students at MIS Bina Dharma Parit Rabu, Teluk Keramat District. This research uses a qualitative approach while this type of research is phenomenological research. There are three types of data collection techniques in this study, namely: Interview, Observation and Documentation. While data analysis techniques used data collection, data reduction, data display, conclusion drawing and verification. Then the data validity checking techniques used are triangulation (source triangulation) and member check. The results of the study are: First, the teacher's strategy in shaping the disciplinary character of students at MIS Bina Dharma Parit Rabu Teluk Keramat District for the 2022-2023 academic year uses several strategies, namely habituation strategies, exemplary strategies, supervision strategies, and punishment strategies. Second, the disciplinary character of grade V students at MIS Bina Dharma Parit Rabu Teluk Keramat District for the 2022-2023 academic year consists of several types of disciplines, namely self-discipline, social discipline, and national discipline. Third, supporting and inhibiting factors in shaping the disciplinary character of grade V students at MIS Bina Dharma Parit Rabu Teluk Keramat District for the 2022-2023 academic year are changes that arise Produce or cause a change or growth, maintain a close relationship between teachers and students, and there is good communication between parents, student teachers and the community environment and the example of teachers, parents and society. While the inhibiting factor is the lack of interest of children and the family environment